2019
DOI: 10.1248/cpb.c18-00844
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of the Effect of Tigecycline on Coagulation Function

Abstract: A number of clinical trials demonstrated that tigecycline was effective and well tolerated in the treatment of patients with various bacterial infections, but few literatures had shown the coagulopathy induced by tigecycline. To address this concern, we performed a retrospective analysis to assess the impact of tigecycline treatment on coagulation parameters in 50 patients with bacterial infections in our hospital (Shandong Provincial Hospital, China). These patients were treated with tigecycline at Shandong P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
(27 reference statements)
7
18
0
Order By: Relevance
“…The liver function of the remaining 10 patients was not impaired during tigecycline treatment, but 3 suffered bleeding events [11,15,20], all of whom took the recommended dose. Regarding the retrospective studies, Routsi et al [12] reported that the bilirubin level did not change significantly, while Zhang et al [13] and Leng et al [24] showed that there was no change in alanine aminotransferase (ALT), aspartate aminotransferase, and creatinine (Cr) levels during therapy. However, Sun et al [16] found that 33 of 59 patients had an elevated ALT or total bilirubin level.…”
Section: Discussionmentioning
confidence: 99%
“…The liver function of the remaining 10 patients was not impaired during tigecycline treatment, but 3 suffered bleeding events [11,15,20], all of whom took the recommended dose. Regarding the retrospective studies, Routsi et al [12] reported that the bilirubin level did not change significantly, while Zhang et al [13] and Leng et al [24] showed that there was no change in alanine aminotransferase (ALT), aspartate aminotransferase, and creatinine (Cr) levels during therapy. However, Sun et al [16] found that 33 of 59 patients had an elevated ALT or total bilirubin level.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the alterations in FIB, aPTT, and PT started to appear four days after the initial dosage, and they worsened over the following days of treatment. In this study, the changes in the coagulation parameters gradually reversed four days after the discontinuation of treatment [20].…”
Section: Discussionmentioning
confidence: 60%
“…These minor changes are of little clinical relevance, as clinical overt bleeding in critical care is mostly linked to gross fibrinogen decreases. Moreover, the fibrinogen decrease in critical ill patients tends to occur only after several days of tigecycline start [3,4]. We conclude that the blood of our healthy subjects lacks either the causative agent of the fibrinogen decrease observed in critical ill patients under tigecycline treatment or a long enough exposure to tigecycline.…”
Section: Discussionmentioning
confidence: 60%
“…A described side effect during tigecycline therapy is coagulopathy. Three small-scale studies reported effects of tigecycline on coagulation [3][4][5]. A clinical trial observed decreased fibrinogen levels as assessed by the classical Clauss method during high-dose treatment with tigecycline in a group of 45 intensive care patients [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation